Pancreatic islet autotransplantation for nonmalignant and malignant indications. Issue 3 (23rd November 2015) - Tanhehco, Yvette C.; Weisberg, Stuart; Schwartz, Joseph
Abstract : The standard therapy for patients with chronic pancreatitis (CP) and severe abdominal pain is total pancreatectomy (TP) followed by islet autotransplantation (IAT) to prevent the development of brittle diabetes. In adult patients, narcotic independence is achieved in up to 73% of patients 1 to 5 years after transplantation whereas insulin independence is achieved in up to 40% of patients 1 to 2 years after transplantation. Pediatric patients have shown similar outcomes for narcotic independence (up to 79%) but better outcomes for insulin independence (up to 56% 1 year after transplantation). The quality of life of both adult and pediatric patients improved significantly after TP‐IAT using the Medical Outcomes Study SF‐36 survey. IAT after pancreatectomy is also performed for patients with benign and malignant disease of the pancreas. The limited studies in this patient population suggest that IAT may be potentially beneficial for carefully selected patients when sufficient numbers of islet cells can be isolated. Further studies involving a larger number of patients are needed to determine the risks and benefits of IAT in patients with malignancy. The feasibility of IAT depends on the availability of a laboratory that can isolate the pancreatic islet cells. An on‐site laboratory is the traditional model; however, remote processing of pancreatic islets has been reported to result in successful outcomes. This review discusses the outcomes of adult and pediatric autologous pancreatic islet cell transplantation for CP and pancreatic tumors as well as laboratory processing of pancreatic islet cells.